Near miss: determinants of maternal near miss and perinatal outcomes: a prospective case control study from a tertiary care center of India. (12th December 2022) - Agarwal, Neha; Jain, Vanita; Bagga, Rashmi; Sikka, Pooja; Chopra, Seema; Jain, Kajal
Abstract: Background/Purpose: To study the causes of maternal near miss and compared maternal and perinatal outcome of maternal near miss cases with controls (women with potential life-threatening complication [PLTC]) and maternal death. Methods: Mothers ( n  = 100) who fulfilled the WHO criteria for maternal near miss (MNM) were identified and enrolled in the study. Two controls for each near miss case were taken. This included the women who had same PLTC but did not reach near miss within one week of enrollment. The comparison of maternal and fetal outcome was done between the two groups and with the maternal death (MD) group, who presented initially as near miss. Results: Obstetric hemorrhage was the most common potential life-threatening complication in MNM and MD group. On multiple logistic regression analysis, we found that the presence of organ dysfunction was the independent predictor of near miss and need of mechanical ventilation and coagulation dysfunction as an independent predictor of maternal death. A mother in the near miss group or death group had a higher chance of giving birth to a still-born child ( p = < 0.001). Risk of neonatal death after NICU admission was numerically more among near miss and death group than controls, although statistically insignificant ( p  > .05) Conclusion: Despite making tremendous progress in obstetric care facilities at a tertiary level, developing countries need to strengthen primary care infrastructure and referral system. To improve maternal care, there should be the provision of health education for all pregnant women and antenatal services should be improved.